Dasatinib tyrosine kinase inhibitor as second and third line therapy in chronic myeloid leukemia: outcome of a Nepalese study - Manandhar, Nora Ranjitkar; Kayashta, Gyan Krishna; Acharya, Paras Kumar (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Dasatinib is indicated as a first line, second line and third line tyrosine kinase inhibitor (TKI) in chronic myeloid leukemia (CML). In our center it is used as a second line or third line therapy in BCR-ABL gene positive CML.Methods: It is a retrospective observational therapy done from June 2015 to May 2018. The purpose of the study is to see the response rates using the second line and third line dasatinib after failing or not tolerating imatinib alone or following a sequential therapy with imatinib and nilotinib.Results: A total of 31 (male 56.3%) patients were included in our study. In eighteen patients it was used as a second line TKI and in 13 a third line TKI. Complete Hematologic Response (CHR) was achieved in 93.55%. Best optimal responses were 46.66% and 61.53% in second and third line dasatinib respectively. Major Molecular Response (MMR) was achieved in 35.71% (26.66% and 46.14% in second line and third line dasatinib respectively). For both the groups, the overall survival was 92% and 94 % at 20 months and the event free survival was 70% at 10 months.Conclusions: Dasatinib is effective in achieving MMR and inducing survival benefit in the patients who failed imatinib alone and imatinib and nilotinib.